Culture of «green» festivals in urbanized space: the case of «Kharkiv Green Urban Fest 2023» - Deineko Oleksandra; Zaporozhchenko Ruslan; Yashkina Daria (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The article is devoted to highlighting the culture of festivals on the example of the urbanized space of the city of Kharkiv through the prism of the ecological festival «Kharkiv Green Urban Fest 2023», which was held by the School of Sociology at V.N. Karazin Kharkiv National University on June 17, 2023, based on the cultural space «YermilovCenter». The festival was held as part of the implementation of the international research project FUSILLI (Fostering the Urban Food System Transformation through Innovative Living Labs Implementation) at the School of Sociology of V.N. Karazin Kharkiv National University, funded by the European Union’s Horizon 2020 Research and Innovation Program under the grant agreement №101000717. The main objective of the festival was to showcase local initiatives that focus on responsible consumption, farming, recycling, social entrepreneurship, healthy eating, and sustainable development. In this article, based on small semi-structured interviews with event participants, we propose a conceptualization of festival culture and identify its inherent features, at the normative-value and structural-functional levels. Using some methodological approaches, we propose to consider the culture of festivals as an example of spontaneous social (inter)action, during which subjects are involved in the construction of a new social reality, which can, although not necessarily, be exported to their own environment. This example of social (inter)action helps to disseminate certain values and beliefs that can be shaped by interactional actions. In addition, we demonstrate the importance and necessity of such events to promote the values of responsible consumption and the development of the city’s food system.